Osimertinib: Another medication related to osteonecrosis of the jaws? A case report and literature review - Wang, Feng; Wei, Shengnan; Zhang, Zexuan; Zhang, Yuan; He, Jingya; Sun, Bin (Frontiers in Pharmacology, 2022)
Introduction: Medication-related osteonecrosis of the jaw (MRONJ) is an oral complication in cancer patients being treated with either antiresorptives, mainly denosumab and bisphosphonates, or antiangiogenic drugs. Osimertinib is a third-generation epidermal growth factor receptor (EGFR)-tyrosine kinase inhibitor (TKI) for the treatment of patients with EGFR T790M advanced non-small-cell lung cancer (NSCLC). TKI-induced osteonecrosis of the jaw has been reported in recent years, but these cases almost occur in combination with bisphosphonates, and the data on MRONJ associated to osimertinib is scarce. Case report: We reported a case of MRONJ associated only with osimertinib. A 69-year-old female patient with NSCLC developed MRONJ after 4 years of treatment with osimertinib. Six months ago, she felt persistent pain and swelling in the right maxilla. After three months of pain, her dentist extracted one tooth in the right maxilla under local anesthesia. We examined her gingiva and found fistula and pus spillage. A digital volume tomography scan revealed sequestrum. The patient underwent surgical debridement of the necrotic bone under general anesthesia and administered intravenous antibiotics at the hospital. Histopathological analysis of the bone biopsy revealed a diagnosis of MRONJ. Conclusion: This report provides evidence that osimertinib monotherapy can cause MRNOJ, and has a contribution to explore the formation mechanism of MRONJ. For those patients who take osimertinib, routine oral examinations and monitoring should be performed before and during treatment, as well as prompt closure of wounds and antibiotic treatment to avoid infection after invasive oral surgery such as tooth extraction.